Designing polymeric adhesives for antimicrobial materials: poly(ethylene imine) polymer, graphene, graphene oxide and molybdenum trioxide – a biomimetic approach. Issue 32 (24th May 2017) - Nguyen, Hang N.; Nadres, Enrico T.; Alamani, Bryan G.; Rodrigues, Debora F.
Abstract : The synthesis of biocompatible polymers for coating applications has gained significant attention in recent years due to the increasing spread of infectious diseases via contaminated surfaces. Abstract : The synthesis of biocompatible polymers for coating applications has gained significant attention in recent years due to the increasing spread of infectious diseases via contaminated surfaces. One strategy to combat this problem is to apply antimicrobial coatings to surfaces prone to microbial contamination. This study presents a series of biomimetic polymers that can be used as adhesives to immobilize known antimicrobial agents on the surfaces as coatings. Several polymers containing dopamine methacrylate as co-polymers were synthesized and investigated as adhesives for the deposition of an antimicrobial polymer (polyethyleneimine) and antimicrobial nanoparticles (graphene, graphene oxide and molybdenum trioxide) onto glass surfaces. The results showed that different antimicrobials required different types of adhesives for effective coating. Overall, the coatings fabricated from these composites were shown to inactivate E. coli and B. subtilis within 1 h. These coatings were also effective to prevent biofilm growth and demonstrated to be non-toxic to the human corneal epithelial cell line (htCEpi). Leaching tests of the coatings proved that the coatings were stable under biological conditions.